The Impact of Differentiated Instruction on Students’ Performance in Critical Reading - Sahril Sahril; Auliyanti S N; Muh. Safar Nur (Makassar State University, 2021)
Abstract. This research shows the importance of reading in various settings in critical reading learning. This research involves a study to improve two classes' experience and two students of Universitas Negeri Makassar in their critical reading class about their reading level during one semester by implementing a differentiated instruction model. The results showed a positive effect that differentiated instruction in critical reading learning on students' reading interest and reading level. Differentiated Instruction learning model by chances for students having an in-depth view of the target language, learning to look at their abilities in new ways, increasing their self-confidence, and using English to communicate and achieve authentic communication as an EFL learning goal. It is assumed that most participants see the Differentiated Instruction learning model as an effective means of facilitating communication and understanding in Critical Reading lecture.Keywords: Critical Reading, Differentiated Instruction Model